Non-abelian 4-d black holes, wrapped 5-branes, and their dual descriptions - Gubser,SS; Tseytlin,AA; Volkov,MS (Journal of High Energy Physics, 2001)
We study extremal and non-extremal generalizations of the regular non-abelian monopole solution of [23], interpreted in [9] as 5-branes wrapped on a shrinking S2. Naively, the low energy dynamics is pure N = 1 supersymmetric Yang-Mills. However, our results suggest that the scale of confinement and chiral symmetry breaking in the Yang-Mills theory actually coincides with the Hagedorn temperature of the little string theory. We find solutions with regular horizons and arbitrarily high Hawking temperature. Chiral symmetry is restored at high energy density, corresponding to large black holes. But the entropy of the black hole solutions decreases as one proceeds to higher temperatures, indicating that there is a thermodynamic instability and that the canonical ensemble is ill-defined. For certain limits of the black hole solutions, we exhibit explicit non-linear sigma models involving a linear dilaton. In other limits we find extremal non-BPS solutions which may have some relevance to string cosmology.